APPLICATION OF THE JIGSAW LEARNING MODEL ASSISTED WITH AUDIO VISUAL MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES ON DIVERSITY MATERIALS IN CLASS IV SDN RANTO PANYANG 1 MEUREUBO - lindawati, lindawati; Husin, M.; Fitri, Aida (Universitas Syiah Kuala, 2024)
This research aims to improve social studies learning outcomes after implementing the Jigsaw learning model assisted by Audio Visual Media to improve student learning outcomes in diversity material in Class IV Ranto Panyang Meureubo in 2022/2023. This research is a type of classroom action research carried out in two cycles and in Each cycle consists of 4 stages, namely planning, action, observation/evaluation, and reflection. Each cycle is carried out in 2 meetings consisting of 1 meeting to teach the material, 1 meeting to carry out evaluation. The research subjects were 30 grade IV students at SD Negeri Ranto Panyang 1 Meureubo for the 2022/2023 academic year, consisting of 10 male students and 20 female students. The instrument used in this research is an observation sheet to determine teacher and student activities during the learning process and test learning outcomes. From the results of the analysis, it was found that in cycle I the average score obtained by students was 76.83 and 20 students (66.67%) completed the learning process and 10 students (33.33%) did not complete. . In cycle II the average score obtained by students was 84.5 and 26 students who completed it (86.67%) and 4 students who did not complete it (13.33%). Student activity increased from cycle I to cycle II. This can be seen from the average score in cycle I which was obtained at 69 and in cycle II obtained an average score of 87.5%. Based on these results, the application of the jigsaw type cooperative learning model assisted by audio-visual media can increase teacher and student activity in learning as well as student learning outcomes.